Metal plasmonic nanoarrays for surface-enhanced Raman spectroscopy and applications of atomic layer deposition - Li, Xianglin (2014)
As a powerful spectroscopic technique, SERS has attracted much attention in the past decade due to its wide applications in biological sensing and diagnostics. One major challenge to make SERS as a general analytical tool lies in the design and fabrication of noble metal nanostructure substrates with large and reproducible Raman enhancements over a wide area, ideally using inexpensive, facile, high-throughput method. In this thesis, we utilize a nanosphere lithography (NSL) method combined with atomic layer deposition (ALD) to fabricate 2D metal nanostructure arrays. First, a recyclable SERS substrate comprising ordered arrays of Au semishells on TiO2 spheres is demonstrated. Second, additional metal particles are introduced also with the aid of ALD and metal dewetting to couple with metal bowls or semishell arrays, both show evident further enhancement compared to conventional pure metal semishell arrays. Our results demonstrate the powerfulness of ‘NSL+ALD’ in fabricating ordered array SERS substrates.